Commercialization and Family Farming. The case of El Paseo de la Economía Social y Solidaria of the National University of La Plata: impacts of the COVID 19 pandemic and the ASPO in its territorial configuration - Andrada, Nicolás (Universidad Nacional del Litoral, 2021)
This article presents the experience of El Paseo de la Economía Social y Solidaria of the National University of La Plata in the context of the COVID 19 pandemic and “Mandatory Preventive Social Isolation” highlighting in particular the situation of Family Farmers who participate in it. El Paseo de la Economía Social y Solidaria is a marketing experience in which organizations of horticultural producers of Family Farming participate, along with artisans, honey producers, food producers, etc. It has taken place since 2011, ascribes to the values of the Social and Solidarity Economy of the University Extension policy of the UNLP. As a result of the pandemic and the “Mandatory Preventive Social Isolation”, "El Paseo" went from having fairs located in different UNLP premises to an expanded spatial configuration with more than a hundred delivery points (addresses) located in the center of the city and the neighborhoods. This transformation implies a significant change since although the number of consumers increases and the spatial dimension of the market is extended, the cultural aspects and social and community interaction that the nature of the fair implies are momentarily suspended. These changes in the spatial, economic and cultural dimensions reconfigure the territory, generating a new insertion of El Paseo in the city.